The philosophy of money - Simmel, Georg, 1858-1918 (Routledge, 2004)
This title provides wide-ranging discussions of the social, psychological and philosophical aspects of the money economy, giving insights into the forms that social relationships take. It analyses the relationships of money to exchange, the human personality, the position of women, and individual freedom.
"First published in 1978 by Routledge and Kegan Paul Ltd."--Title page verso
Keywords: Money.; Liberty.; Freedom; Liberté.; freedom.; BUSINESS & ECONOMICS -- Money & Monetary Policy.; Money; Geld.